Enhanced protective properties and UV stability of epoxy/graphene nanocomposite coating on stainless steel - H. Alhumade; A. Yu; A. Elkamel; L. Simon; A. Abdala (eXPRESS Polymer Letters)
Epoxy-Graphene (E/G) nanocomposites with different loading of graphene were prepared via in situ prepolymerization and evaluated as protective coating for Stainless Steel 304 (SS304). The prepolymer composites were spin coated on SS304 substrates and thermally cured. Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM) were utilized to examine the dispersion of graphene in the epoxy matrix. Epoxy and E/G nanocomposites were characterized using X-ray diffraction (XRD) and Fourier Transform Infrared (FTIR) techniques and the thermal behavior of the prepared coatings is analyzed using Thermogravimetric analysis (TGA) and Differential scanning calorimetry (DSC). The corrosion protection properties of the prepared coatings were evaluated using Electrochemical Impedance Spectroscopy (EIS) and Cyclic Voltammetry (CV) measurements. In addition to corrosion mitigation properties, the long-term adhesion performance of the coatings was evaluated by measuring the adhesion of the coatings to the SS304 substrate after 60 days of exposure to 3.5 wt% NaCl medium. The effects of graphene loading on the impact resistance, flexibility, and UV stability of the coating are analyzed and discussed. SEM was utilized to evaluate post adhesion and UV stability results. The results indicate that very low graphene loading up to 0.5 wt % significantly enhances the corrosion protection, UV stability, and impact resistance of epoxy coatings.